Lebanon Cost‑of‑Service and Tariff Design Study - World Bank (World Bank, Washington, DC, 2020)
This report aims to provide a background of the electricity sector in Lebanon and to estimate the current and future costs of the sector in order to inform reform plans that are needed to recover the sector financial viability.